Spiritual Well-Being, Social Support, and Financial Distress in Determining Depression: The Mediating Role of Impact of Event During COVID-19 Pandemic in Iran - Sharif Nia, Hamid; Gorgulu, Ozkan; Naghavi, Navaz; Robles-Bello, María Auxiliadora; Sánchez-Teruel, David; Khoshnavay Fomani, Fatemeh; She, Long; Rahmatpour, Pardis; Allen, Kelly-Ann; Arslan, Gokmen; Pahlevan Sharif, Saeed (Frontiers in Psychiatry, 2021)
This study investigates the relationship between spiritual wellbeing, social support, and financial distress with depressive symptoms due to the COVID-19 pandemic. A path analysis was used to analyze data collected from 1,156 Iranian participants via an online survey. The results showed that spiritual wellbeing and social support were negatively related to depressive symptoms and financial distress. The impact of COVID-19 events showed negative associations with depressive symptoms. In addition, the link between spiritual wellbeing and financial distress with depressive symptoms was partially mediated by the impact of events.